Pectinesterase activity and gene expression correlate with pathogenesis of Phytophthora infestans - Linmei Deng; Xun Huang; Jian Dao; Yajin Xu; Kunyan Zhou; Wenping Wang; Chunjiang Liu; Meng Chen; Shunhong Zhang; Yue Zhang; Jianjun Hao; Xia Liu; et al. (Frontiers in Plant Science)
Late blight caused by Phytophthora infestans is the most devastating disease of potato. Phytophthora infestans produces many secondary metabolites and effector proteins, involved in the pathogenesis, which compromise host defense mechanisms. Pectinesterase (PE) is a cell wall degrading enzyme secreted by P. infestans to infect the host. To examine the role of PE in P. infestans, 15 strains of P. infestans were isolated from infected potato leaves in Yunnan, China. We analyzed the biological effects of exogenously added PE on P. infestans and its activity and gene expression after infection of potato using quantitative real-time polymerase chain reaction (RT-PCR). It was found that PE significantly promotes the growth of P. infestans, increases the weight of mycelium and the number of sporangia, and promotes the sporangial germination. PE accelerated the infection process of P. infestans on potato. The pathogenicity of P. infestans was positively correlated with PE activity and gene expression. PE is a key to the virulence difference of potato late blight.